The Impact of Indonesia’s Economic Growth on Olicy and Global Economic Influence - Natalia Indrawati; syamsul Arifin; Devangga Putra Adhitya Pratama (CV Pena Jaya Pers, 2025)
Indonesia’s economic growth has played a significant role in shaping national policy frameworks and strengthening the country’s position within the global economic system. As the largest economy in Southeast Asia and an emerging middle-income country, Indonesia’s sustained economic expansion has influenced fiscal and monetary policy formulation, trade strategies, investment regulations, and international economic diplomacy. This literature review aims to examine existing academic studies, policy reports, and empirical research related to the impact of Indonesia’s economic growth on domestic policy development and its global economic influence. The review synthesizes findings from various sources to highlight the relationship between economic growth and government policy responses, including macroeconomic stability, foreign direct investment, globalization, and trade integration. Furthermore, the literature indicates that Indonesia’s economic growth has enhanced its participation in regional and global economic forums, increased its attractiveness to international investors, and strengthened its bargaining power in global economic governance. However, several challenges remain, such as income inequality, structural dependency, and vulnerability to global economic shocks. This study contributes to a comprehensive understanding of how economic growth not only drives domestic policy direction but also shapes Indonesia’s evolving role in the global economy.